Building Resilience in Sub-Saharan Africa's Fragile States - Gelbard, Enrique (Departmental Papers; Departmental Paper ;, 2015)
This paper analyzes the persistence of fragility in some sub-Saharan African states and the multiple dimensions of state weakness that are simultaneously at play. This study also provides an overview of the analytics of fragility, conflict, and international engagement with fragile states before turning to an assessment of the current state of affairs and the areas in which there has been progress in building resilience. The paper also looks at the role of fiscal policies and institutions and analyzes growth accelerations and decelerations. Seven country case studies help identify more concretely some key factors at play, and the diversity of paths followed, with an emphasis on the sequencing of reforms. The paper concludes with a summary of the main findings and policy implications.